Financial Convergence Test with Fourier Panel KPSS Stationarity Test: Findings from Fragile Five Countries - Temiz, Mehmet; Konat, Gökhan (My University, 2023)
Financial development is an important component of economic development. In particular, it is very important for developing countries to converge to developed countries in terms of financial development level. In this study, the convergence of the financial development indicators of the Fragile Five Countries to the average of the indicators of the four selected countries (USA, England, Australia and Japan) in the top ten in terms of financial development level for the period 1980-2020 is tested. In this respect, our study contributes to the literature by measuring the convergence of a developed country group, not a single country. The data used in the study were accessed from the World Bank official database. Stationarity test which is introduced to the literature by Nazlıoğlu and Karul (2017) based on the Fourier stationarity test developed first by Becker et al. (2006). This test gives results for both the individual and the panel as a whole. As a result of the tests, it is seen that the financial development indicators of the Fragile Five Countries do not converge to the selected country group and its average. Results showed that, the financial markets of the Fragile Five Countries are in a static structure. Their financial systems do not depth enough and so these systems are far from efficiency. Necessary precautions need to be taken in terms of inadequacy of financial indicators examined. Therefore, it can be inferred that there are weaknesses in financial systems in matters such as economic integration, liberalization, harmonization of regulations and globalization.
Keywords: Financial Development; Liquid Liabilities; Private Loan; Deposit Bank Assets; Fourier Panel Stationarity; Convergence.